(untitled) (Pyramid Journal of Medicine, 2026)
Burnout among resident doctors is a critical global concern, yet Nigeria lacks structured call-hour regulations. This study assessed the prevalence of burnout, its association with duty-hour practices, and explored contextual factors influencing residents’ well-being. A concurrent mixed-methods study was conducted among 300 residents in Kano tertiary hospitals, which included a self-administered survey on work-hour practices and the Maslach burnout inventory, and was analyzed using descriptive statistics and Chi-square tests using the Statistical Package for Social Sciences (SPSS) version 27; Focus Group Discussions (FGDs) and Key-Informant Interviews (KIIs) explored contextual factors. The mean age of participants was 32.50 (Standard Deviation, SD=4.85). Emotional exhaustion was reported by 89.3% of participants, depersonalisation by 48.3%, and low personal accomplishment by 47.7%. The overall prevalence of burnout was 63.7%. Burnout was directly proportional to call duration (p<0.001) and inversely related to post-call rest hours (p<0.001). Additional drivers included inadequate amenities, poor mental health support, staff shortages, unfair remuneration, and workplace insecurity. Burnout among Nigerian resident doctors is at epidemic levels, driven by unregulated call hours and systemic factors, requiring urgent reform through structured call-hour policies, mental health services, and improvements in staffing, infrastructure, and safety.